Evaluation of Vaccination Strategy Against Rabies in Hong Kong Macaques - Martelli, Paolo; St-Hilaire, Sophie; Hui, Wai-Suk; Krishnasamy, Karthiyani; Magouras, Ioannis; Nekouei, Omid (Frontiers in Veterinary Science, 2022)
The objectives of this study were to assess the serological response to rabies vaccination in Hong Kong macaques and provide evidence-based recommendations for the vaccination interval implemented by the Government of Hong Kong. An inactivated rabies vaccine was administered subcutaneously to captured macaques under a mass sterilization program in Hong Kong. Blood samples from the animals were collected in a 2015 field survey and stored in -80℃ freezer. In 2021, the frozen sera from vaccinated animals were prepared and tested for antibodies against the rabies virus using a commercial blocking enzyme-linked immunosorbent assay (ELISA) test. Sixty-five samples were available from the vaccinated macaques that had received at least one dose of the vaccine between 2008 and 2015. The interval between the first vaccination and blood sampling ranged from 21 to 2,779 days (median: 990). Only five macaques had a second vaccination record at the sampling time, all with high antibody levels. Among the remaining macaques, 77% (46/60) were positive for rabies antibodies. No specific association was observed between the post-vaccination period and the antibody titer of these macaques, and no adverse reactions were reported. Although the precise level of protection against a potential challenge with the rabies virus cannot be ascertained, the vaccination elicited rabies antibodies in 87% (21/24) of the macaques tested within 2.5 years of their first vaccination. Our findings indicate the potential benefits of the current vaccination strategy to protect the population from rabies and consequential mandatory culling of all macaques if a natural infection occurs.